Coordinated WECS–BESS Control for Frequency Resilience Enhancement in Low-Inertia Power Systems - Andi Syarifuddin; Muhammad Naim; Amelya Indah Pratiwi (International Journal Of Electrical Engineering and Inteligent Computing, 2025)
The growing dominance of power-electronics–interfaced renewable resources, particularly wind energy conversion systems (WECS), has led to a substantial reduction in system inertia, posing significant challenges to frequency resilience in modern power grids. Previous national-scale studies on a 23-bus equivalent transmission system have highlighted degraded dynamic performance under high wind penetration; however, active mitigation strategies were not incorporated. This paper extends that work by developing and validating a coordinated control framework combining virtual inertia and adaptive droop mechanisms implemented on Battery Energy Storage Systems (BESS) and DFIG-based WECS. A modified IEEE 23-bus model, scaled from the scaled to represent a national transmission grid, is simulated in MATLAB/Simulink to evaluate performance under various wind penetration and fault conditions. Simulation results demonstrate that the proposed coordinated control improves transient frequency resilience reducing the rate of change of frequency (RoCoF) by up to 38%, increasing frequency nadir by 0.43 Hz, and accelerating voltage recovery within grid-code limits. The MATLAB/Simulink workflow provides a reproducible validation platform for coordinated grid-forming strategies. The proposed approach effectively addresses the low-inertia limitation identified in the previous study and establishes a scalable framework for future techno-economic optimization and hybrid renewable integration in national power systems.